Counseling and Demonstration in Efforts to Prevent Diarrhea in Early Childhood in Taba Baru Village, North Lubuklinggau District I - North, Gustin Widya; Surahman , Fery; Amallia , Herica; Yati, Meri; Susanti, Maya; Elvina, Siska Rosa (Universitas Dehasen Bengkulu, 2025)
Diarrhea is one of the leading causes of morbidity among early childhood. In Lubuklinggau Utara I Subdistrict, Lubuklinggau City, South Sumatra Province, the incidence of diarrhea is relatively high, with 11 reported cases—particularly in the Taba Baru subdistrict, which has been affected by viral and bacterial infections due to poor hygiene and sanitation practices.The 2025 Thematic Community Service Program (KKN-T) of Dehasen University Bengkulu focused on diarrhea prevention through an educational approach, including diarrhea counseling, leaflet distribution, handwashing with soap demonstrations, and practical sessions on how to prepare homemade oral rehydration solution (ORS). This activity was conducted in collaboration with the parents of children enrolled at Paud KB Raudhatul Jannah (RJ). The results showed an increase in parental awareness regarding the importance of home and environmental cleanliness, proper handwashing with soap, and the preparation of homemade ORS—all aimed at promoting clean and healthy living and reducing the risk of diarrhea. This program has proven effective as a promotive and preventive strategy based on early childhood interventions, serving as a potential model for implementation in other regions. Cross-sector collaboration and continuous education are essential to support efforts to reduce the incidence of diarrhea and contribute to stunting prevention through improved early childhood health.